A New Global Climate Agreement: Implications for Agriculture?. (August 2015) - Blandford, David; Hassapoyannes, Katharina
Summary Although agriculture is a relatively emissions‐intensive sector in many countries, it is unlikely to be centre stage in upcoming negotiations on a climate change agreement to be held in Paris in December 2015. Nevertheless, the agricultural sector is a major user of energy. It is therefore likely to be affected by higher costs in upstream and downstream industries resulting from domestic policies to reduce greenhouse gas emissions (GHGs). National differences in emissions reduction commitments and their implementation may result in different implicit prices for carbon across countries. For a relatively high emitting sector like agriculture, smaller adjustments in output would be needed to satisfy a GHG reduction requirement, but adjustment may be more costly if anticipated increases in global food demand are to be met. This could have distributional implications between developed and developing nations due to changes in food prices and the composition of demand. If measures taken to reduce emissions in other sectors are successful, the increasing proportion of total emissions generated by agriculture could become a focus of attention. Agriculture is likely to become more prominent in the climate change debate and will have to play a much greater role in future global climate change policies.